Prevalence of Metabolic Syndrome in Diabetic Patient - UK Khan, UK Khan; Dipta, TF; Faruque, MO; Sarder, K; Sultana, SSS; Nahar, Q (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background: Factors associated for the development of metabolic syndrome vary from region to region and race to race. Objectives: The present study aimed to assess the prevalence of metabolic syndrome and phenotype of newly diagnosed IGT and DM subjects. Methods: In this cross sectional study 100 DM and 44 IGT subjects recruited from OPD BIRDEM hospital. BMI, Neck, and waist circumference, WHR and blood pressure were collected by skilled trainer using modern equipments. Serum glucose was measured by glucose-oxidase method and lipid profile was measured by enzymatic-colorimetric method. Results: Glycemic status was higher in diabetic subjects (12±5; ABF 18±6) than IGT subjects (FPG 6±0.84; ABF 9±2). About 39.6% subjects had metabolic syndrome according to the definition of EGIR and 21.9 % were hypertensive in DM subjects. Neck circumference was positively correlated with BMI (r=0.4, p=0.02) and waist circumference (r=0.25.p=0.003). Conclusions: Glycemic status affects at the BMI 24 and neck circumference 33cm with age 40 years. About 39.6 % MS present following EGIR but poor % MS have found following ATP III and WHO criteria DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11409 J Bangladesh Coll Phys Surg 2012; 30: 85-90